378 Cervical adenocarcinoma. What is the reason for referral?. (13th November 2020) - Cervantes, P; Altamirano, R; Nazzal, O; Lagos, A; Solari, M; Pincheira, E; Rojas, J; Suarez, E
Abstract : Introduction: The objective of this presentation is to evaluate the reason for referral of patients with a diagnosis of cervical adenocarcinoma treated in the Cervical Pathology Unit of the Hospital San Borja Arriaran. Material and Method: Retrospective analysis of records of patients treated for cervical adenocarcinoma, between the years 2008 to January 2019. Results: Of 5353 positive cytologies studied between January 2008 and January 2019, a total of 105 adenocarcinoma were found, with a median age of 47 years (between 20 to 85 years). Out of these 105 patients: 15% were referred due to clinical suspicion, of which 5 patients (30%) had a visible tumor; and 89 patients (85%) were referred due to altered cytology, corresponding to 2% of the total. Analyzing the cytology that originated the referral of these 89 patients with abnormal results, 41.5% (37) had a PAP suggestive of adenocarcinoma, 6.7% (6) were suggestive of squamous carcinoma, 28% (25) had a PAP NIE II-III, and 23.5% (21) had an atypical in one of its three varieties [double non-specific atypical: 9.5% (2), glandular atypical: 47.6% (10) and atypical that does not exclude high-grade injury 42.8% (9)]. Conclusions: Cervical adenocarcinoma is an emerging entity and it is difficult to diagnose. Screening programs do not necessarily decrease its incidence, on the contrary, they have become the main source of referral for cervical adenocarcinoma. In our review, it corresponded to 85% of the cases. Despite the difficulty of investigating an adenocarcinoma through PAP, this was the main cause of referral. The referral for clinical suspicion corresponded to 15%.